Pengaruh Sistem Informasi Akuntansi Manajemen dan Desentralisasi terhadap Kinerja Manajerial pada PT. Bank Rakyat Indonesia Cabang Kabupaten Bantaeng - Khusnul Khatima Asrul; Ismail Badollahi; Wa Ode Rayyani (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Managerial performance has become a critical factor in maintaining organizational competitiveness within the increasingly dynamic banking industry. The effectiveness of managerial decision-making is closely associated with the availability of relevant management accounting information and the delegation of authority within the organization. Despite extensive discussions regarding the role of Management Accounting Information Systems (MAIS) and decentralization, empirical findings remain inconsistent, particularly in the context of regional banking institutions. A quantitative approach with a causal associative design was employed at PT. Bank Rakyat Indonesia Branch of Bantaeng. The study involved 36 permanent employees selected through a saturated sampling technique. Data were collected using questionnaires, observations, and documentation, and subsequently analyzed using multiple linear regression. The findings indicate that Management Accounting Information Systems have a positive and significant effect on managerial performance. Decentralization also demonstrates a positive and significant contribution to managerial performance. Furthermore, both variables simultaneously exert a significant influence on managerial performance, indicating that the availability of timely, integrated, and relevant information, supported by appropriate delegation of authority, enhances managerial effectiveness. The model explains 53.8% of the variation in managerial performance, while the remaining variation is attributable to other organizational factors. These findings reinforce the contingency perspective, emphasizing the importance of aligning information systems and organizational structure to improve managerial outcomes in the banking sector.